2016
DOI: 10.1007/978-3-319-27006-7_2
|View full text |Cite
|
Sign up to set email alerts
|

Eutrophication and the Ecosystem Approach to Management: A Case Study of Baltic Sea Environmental Governance

Abstract: This study investigates if and how present institutional structures and interactions between scientifi c assessment and environmental management are suffi cient for implementing the ecosystem approach to management (EAM) in the case of Baltic Sea eutrophication. Concerning governance structures, a number of institutions and policies focus on issues relating to eutrophication. In many cases, the policies are mutually supportive rather than contradictory, as seen, for example, in the case of the mutually support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…It can be argued that this occurred when the Nest system quite directly influenced the nutrient reduction targets formalised in the BSAP (cf. Karlsson et al, 2016). Still, despite close interaction between HELCOM and Baltic Nest during the development of the 2007 BSAP, the experts linked to Baltic Nest stayed in a traditional knowledge-provider mode by presenting modelling results and scenarios to policy-makers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be argued that this occurred when the Nest system quite directly influenced the nutrient reduction targets formalised in the BSAP (cf. Karlsson et al, 2016). Still, despite close interaction between HELCOM and Baltic Nest during the development of the 2007 BSAP, the experts linked to Baltic Nest stayed in a traditional knowledge-provider mode by presenting modelling results and scenarios to policy-makers.…”
Section: Discussionmentioning
confidence: 99%
“…Eutrophication governance in the Baltic Sea is a complex multi-level governance arrangement, where the international level via EU legislation and HELCOM recommendations and action plans play a dominant and steering role (Karlsson, Gilek, & Lundberg, 2016). National measures are also important for implementing the international policies and to give effect to national policy priorities.…”
Section: Case Study Selectionmentioning
confidence: 99%
“…We found that EU agricultural policy indicators are primarily focused on three SDGs: zero hunger (SDG 2), decent work and economic growth (SDG 8) and life on land (SDG 15). EU agricultural indicators are missing entirely for good health and well-being (SDG 3), gender equality (SDG 5), life below water (SDG 14) and good governance through institutions (SDG 16) (Figures 3-5)issues that have all been highlighted as important for agriculture by the FAO (FAO, 2017(FAO, , 2018 and other scholars (Begashaw & Rockström, 2017;Jansson et al, 2019;Karlsson et al, 2016). Other assessments, too, have found gaps in agricultural policy and the SDGs.…”
Section: Key Findings In Contextmentioning
confidence: 99%
“…Although cognitive interplay exists between the three EU policy initiatives, it is even more evident between the EU and HELCOM, especially between the MSFD and the BSAP (Backer et al 2010;van Leeuwen, van Hoof, and van Tatenhove 2012;van Tatenhove et al 2014;Wenzel 2011;Karlsson, Gilek, and Lundberg 2016). Before the MSFD was developed the EAM was not yet established as the guiding principle of EU marine policy.…”
Section: Interplay Through Cognitionmentioning
confidence: 99%